Study of the effect of human placenta hydrolysate in a new model of metabolic-associated fatty liver disease with iron overload - T. E. Bogacheva; O. A. Gromova; I. Yu. Torshin; V. I. Demidov; A. G. Kalacheva; A. A. Garanin; I. V. Gogoleva; L. E. Fedotova; O. A. Limanova; А. N. Mnatsakanyan; N. Yu. Zhidomorov; T. R. Grishina (Фармакоэкономика, 2025)
Background. The combination of metabolic-associated fatty liver disease (МAFLD) with iron overload occurs in approximately 1/3 of patients and is extremely difficult to treat. In addition to the fact that no specific treatments have been developed for this МAFLD form, there are also few experimental models on which such agents could be tested.Objective: to create a MAFLD model and to study the effectiveness of using human placenta hydrolyzate (HPH) in experiment.Material and methods. In experiment, the rats were divided into three groups: Group 1 was on a normal diet and drinking water, in Groups 2 and 3, a model of liver iron overload was reproduced by intraperitoneal administration of iron sulfate for 12 days under conditions of adding saturated fats (palm oil) and fructose to the diet. On Day 13 of the study, blood was collected from animals in Groups 1 and 2 for biochemical testing and autopsy material (liver, kidneys, brain, heart) for histopathological examination. In Group 3, standardized HPH was administered in a therapeutic dose intramuscularly for 4 weeks. On Day 41, blood and autopsy material were collected. The model was used to test the effectiveness of using standardized HPH and to characterize complex changes in more than 20 biomarkers of liver and kidney functions, hematopoiesis, inflammation, and thrombus formation.Results. HPH injections were shown to be an effective treatment for iron overload МAFLD. Specifically, after reproducing the model on Day 41, levels of ferritin (intact: 201±45 μg/l; model: 254±12 μg/l; p<0.0001), aspartate aminotransferase (AST) (intact: 114.9±27.3 U/l; model: 301,3±30,3 U/l; р<0.000001), alanine aminotransferase (ALT) (intact: 22.8±3.2 U/l; model: 58.7±5.5 U/l; p<0.00014), leukocytes (intact: 4.6±1.3×109 cells/l; model: 6.9±0.8×109 cells/l; p<0.01), thrombocytes (intact: 509.7±121.6×109 cells/l; model: 820.2±50.5×109 cells/l; p<0.01) increased reliably. Total protein levels (intact: 46.2±2 4.6 g/l; model: 45.5±5.8 g/l; p=0.002), serum creatinine (intact: 35.7±1.2 μmol/l; model: 23.3±1.4 μmol/l; p<0.00001) and glomerular filtration rate (GFR) (intact: 169±5 ml/min/1.73 m2; model: 154.1±7.1 ml/min/1.73 m2; p=0.04) decreased. HPH administration resulted in normalization of the listed indicators of polyorgan pathology on Day 41: reliable reduction of ferritin (141±24 μg/l; p<0.001), AST (166.7±51.3 U/l; p=0.00±77), ALT (36.4±7.2 U/l; p=0.00001), leukocytes (4.5±2.7×109 cells/l; p=0.039), thrombocytes (639.0±92.3×109 cells/l; p=0.00157) and reliable elevation of total protein (55.9±3.8 g/l; p=0.0014), normalization of creatinine (27.7±1.5 μmol/l; p=0.0002), and GFR (169.8±6.2 ml/min/1.73 m2; p=0.0011). Histological analysis revealed that HPH promoted hepatic iron excretion while preventing renal, brain, and myocardial damage in the proposed iron-overload МAFLD model.Conclusion. The administration of standardized HPH is effective and safe in the therapy of experimental iron overload МAFLD and prevents polyorgan pathology.